Innovation for Territorial Competitiveness: An Analysis of Bahía Blanca Small and Medium Sized Enterprises (Revista LIDER, 2020)
This article analyzes the innovation capacities of a group of firms from thelocality of Bahia Blanca. Using a Logit model, one concludes that the innovation of the firms is related to the ages of the owners, the employees´ skills, the contacts made with corporate unions and other variables.